Criminal injuries compensation: protecting vulnerable applicants - Guthrie, Rob (Thomson, 2015)
Each year large numbers of persons sustain injury as a consequence of criminal behaviour. All Australian jurisdictions provide State-funded compensation to those harmed in this way. In the case of vulnerable applicants, the Assessor must consider not simply the appropriate and fair amount of compensation, but also how a person will be affected by the payment of compensation. Often a vulnerable applicant will apply through a guardian or a public trustee, although many apply in person. This article examines the use of legislative provisions, rules, regulations and practices in the various Australian jurisdictions in relation to how vulnerable applications may be protected and supported once an award of compensation is made in their favour. Most jurisdictions provide for a mechanism by which compensation may be held in trust where the Assessor considers that the applicant may be unable to manage his or her financial affairs in his or her best interests. This article explores what factors are taken into account by Assessors in the absence of and pursuant to legislative directions. It considers how the approach may vary across jurisdictions and creative approaches to financial protection of vulnerable applicants.